FLEKSIBILITAS TRADISI PESANTREN TERHADAP KEKERASAN PADA ISTERI (STUDI KASUS PADA PENERAPAN UU PKDRT DI LINGKUNGAN PESANTREN KAB. JOMBANG) - Heppy Hyma Puspytasari (Universitas Pendidikan Ganesha, 2021)
The pesantren community has actually been aware of the issue of domestic violence (KDRT) for a long time, but that does not mean they really understand the meaning of domestic violence as a whole. Because in reality, domestic violence itself is hidden in the world of pesantren households. Other things that may also be the cause of the occurrence of domestic violence in the pesantren are the kyai's patrons as leaders of the pesantren who cannot be shaken by anything. Many facts also support that the words of the kyai are always true and never wrong, because he is considered the most understanding of religious teachings. Apart from that, the existence of a verse which states about the nusyus of a wife, and the family study which says